A review of drying technology in tea sector of industrial, non-conventional and renewable energy based drying systems. (April 2023) - Kumar, K. Ravi; Dashora, Kavya; Kumar, Shantanu; Dharmaraja, S.; Sanyal, S.; Aditya, Kaustav; Kumar, Raju
Highlights: Importance of drying of tea is addressed to produce a stable product. Studies on ECP and FBD/VFBD driers are summarized. Studies on MW, RF, and superheated steam tea driers and their challenges are discussed. Investigation on renewable energy-based tea driers and their importance are incorporated. Solar based tea drying system integrated with thermal energy storage is proposed. Abstract: Drying is an important process in the tea processing industry. Drying arrests enzymatic reactions to produce a stable product with increased shelf life. Development of the quality attributes such as taste, fragrance, color, etc. in tea is initiated during processing steps prior to drying, which undergoes the final stage of development during drying to produce the characteristic features of the final product as made tea. In this article, investigations on the drying of tea leaves using industrial/commercially successful driers, such as, endless chain pressure drier, fluidized bed drier and vibro-fluidized bed drier have been discussed. Additionally, investigations on the driers under research stage, such as microwave drier, superheated steam drier and radio frequency drier have also been explored. Drying is an energy intensive process in the tea factory. It consumes 3.5–6 kWh of thermal energy per kg of made tea. Fossil fuels are primarily utilized in the tea factories to meet the thermal energy demand of drying. The specific carbon dioxide emission of tea factories is found in the range of 2.15 to 2.86 kg per kg of made tea. Several attempts have been made to develop the renewable energy based drying system to meet the energy requirements in the tea factories and to minimize the greenhouse emissions. This study also reports past works on renewable-energy-assisted tea drying. Apart from this, study proposes solar energy-based tea drying system along with thermal energy storage and/or integrated with fossil fuel-based furnace.